Reconstructing the Adaptive Performance Management Model in the Dynamics of Flexible and Hybrid Work in the Digital Era - Risnawati; Junaidi, Ahmad; Sunarmin (ADMAN: Journal of Contemporary Administration and Management, 2025)
This study aims to reconstruct the adaptive performance management model within the context of flexible and hybrid work dynamics in the digital era. The research approach used is a literature review with a qualitative method and descriptive analysis. Data was collected from Google Scholar and several credible websites for the period 1991–2025, initially comprising 30 articles, which were then filtered down to 17 most relevant articles through a stringent selection process. The research findings show that traditional performance management models need to transform into more adaptive systems by integrating agile principles, the use of digital technology, self-determination theory, goal-setting theory, and dynamic capability theory. In hybrid and flexible work environments, performance is more effectively assessed using an outcome-based approach, continuous feedback, and real-time digital platforms. This research also highlights the importance of new competencies for managers to manage remote team performance and the need to prioritize employee psychological well-being within the adaptive performance management system. Case studies from various multinational companies support these findings, where flexible performance management approaches have enhanced productivity and employee engagement. This research is expected to serve as a foundation for organizations to develop performance management systems that are more relevant to the demands of modern work.